Harnessing in-plane optical anisotropy in WS2 through ReS2 crystal - Kwon Soyeong; Yun Tae Keun; Ma Peiwen J.; Nam SungWoo (Nanophotonics)
In this work, we explore how the optical properties of isotropic materials can be modulated by adjacent anisotropic materials, providing new insights into anisotropic light-matter interactions in van der Waals heterostructures. Using a WS2/ReS2 heterostructure, we systematically investigated the excitation angle-dependent photoluminescence (PL), differential reflectance, time-resolved PL, and power-dependent PL anisotropy of WS2. Our findings reveal that the anisotropic optical response of WS2, influenced by the crystallographically low symmetry and unique dielectric environment of ReS2, significantly impacts both the optical and temporal behavior of WS2. We observed that the emission anisotropy increases with optical power density, highlighting that anisotropic localization of photo-generated carriers and subsequent charge transfer dynamics are key contributors to the polarization-sensitive optical response. These findings provide a framework for leveraging optical density-sensitive anisotropy mirroring to design advanced anisotropic optoelectronic and photonic devices.